Pengaruh Pembelajaran Inovatif Terhadap Kreativitas Siswa Pada Mata Pelajaran SKI di Kelas IX MTs Al-Irsyadiyah - Purwita, Mita; Supriadi, Dedi; Rosidah, Noneng Siti (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Based on the author's observations on grade IX MTs Al-Irsyadiyah students, Bogor Regency. Some students still have difficulty being active in material they do not understand and are less able to express their opinions while studying. The purpose of this study is to determine the implementation of Innovative learning in SKI subjects and to determine the influence of Innovative learning on student creativity in SKI subjects. The method used in this study is quantitative with a field research approach to obtain or collect information about the influence of learning on the creativity of grade IX students at MTs Al-Irsyadiyah Bogor Regency. Then a simple linear regression test was carried out using SPSS 22 to determine the significant results of the effect of innovative learning on the creativity of grade IX students in MTs. Al-Irsyadiyah Bogor with the T test. If T is calculated with a significant level of 0.05% with free degrees (df) = N-2 (38-2) = 36, Tcalculate = 2.707 > Ttable 1688. Because Thitung > Ttabel, Ho was rejected and Ha was accepted, which means that there is an influence of innovative learning on the creativity of grade IX students at MTs Al-Irsyadiah, Bogor Regency Keywords: . Innovative learning, SKI subjects, students creativity